Management of excess standing biomass in Argentinean grasslands to increase grass and livestock productivity - Kurtz, Ditmar Bernardo (Faculty of Agricultural Sciences, University of Hohenheim, 2019)
Tesis de doctorado para obtener el grado de Ph.D. en Agricultural Sciences presentada en la Facultad de Ciencias Agrarias de Universidad de Hohenheim, en 2016